Brachial plexus palsy following a training run with a heavy backpack. Issue 4 (14th October 2013) - McCulloch, Robert; Sheena, Y; Simpson, C; Power, D
Abstract : A 23-year-old male British soldier developed a progressive sensory loss and weakness in his right arm during a 12 km training run with a load of approximately 70 kg. There was no recovery of his symptoms within 3 months and both MRI and USS did not demonstrate a site of compression within the brachial plexus. An infraclavicular brachial plexus exploration was performed 11 months after injury that indicated an ischaemic neuropathy with post-injury fibrosis. Injuries of the brachial plexus secondary to carrying a heavy backpack during prolonged periods of exercise are rare, particularly in the infraclavicular region. Cases such as this highlight that training regimens within the military population should be appraised due to the risk of similar injuries occurring.